Building higher value-added firm practices in challenging contexts: formal networks and talent management in Turkey - Demirbag, Mehmet; Tatoglu, Ekrem; Wood, Geoffrey; Glaister, Alison J.; Zaim, Selim; Nair, Smitha R. (Sage, 2025)
Where do high-impact human resources management practices thrive, and how do they make a difference in environments with limited institutional support? This study delves into the realm of talent management (TM) in Turkey, where institutional coverage is incomplete and unstable. Drawing on survey data, we explore the conditions under which TM succeeds, supplementing previous research on internal networks by examining the impact of external networks that encompass the entire firm. We find that when firms have closer ties with customers, suppliers and competitors (and hence, the basis for formal network tie building), TM is more prevalent and more likely to be successful. While conventional wisdom in comparative institutional literature suggests that such dense ties might be less effective in emerging markets owing to the absence of advanced complementarities found in mature economies, our study challenges these assumptions. In the eyes of managers, TM is not merely a tool to overcome disadvantages; it is perceived as a source of opportunities. This prompts a critical question: what specific advantages does the emerging economy system confer on firms embracing TM? Our study seeks to unravel these dynamics and contribute to a deeper understanding of the interplay between institutional contexts and TM.
Keywords: complementarity; emerging markets; talent management; Turkey; uncertainty